LITERASI INVESTASI BAGI GENERASI Z PADA SMK KARYA PEMBANGUNAN DI KABUPATEN TANGERANG - Atmaja, Sena; Perwitahasari, Resy; Naim, Abu; Hadi, Helmas Septiyo; Dadang, Dadang; Rosidawaty, Rosidawaty; Wangsih, Ingkak Chintya; Ambarwati, Rina; Gumilang, Andika Mugi; Aminudin, Dindin; Sugiyono, Sugiyono; Ulinuha, Nor Fattah; Faroqi, Fachmi Al; Maesaroh, Siti (Universitas Mataram, 2025)
The Faculty of Economics and Business at Muhammadiyah University A.R. Fachruddin is implementing a community service program with the theme